Reabilitação neuroclusal pelo método das Pistas Diretas Planas - Teruel, Gabriela Peres [UNESP] (2018)
Occlusions diseases are in the public health problems due to their high epidemiological dimension during the infantile phase and are considered by the World Health Organization the third dental problem in public health. Among them, cross bites are highlighted, which is the inability of the two arches to occlude normally in the lateral or anteroposterior relationship. If not solved with an early intervention, it can compromise the craniofacial structure, the structures of the stomatognathic apparatus, the social and psychologi cal interaction of the individual. In this way, it is appropriate to apply preventive methods in order to reduce these public health ills, as well as to ensure the quality of life of patients. The objective of Chapter 1 was to report a clinical case of a child with unilateral posterior crossbite treated with the planas direct tracks method and in Chapter 2 to evaluate the effectiveness of the neuroclusal rehabilitation with the use of planas direct tracks through the analysis of models of gypsum and panoramic radiographs. It is a clinical study, following the RNO protocol with the use of planas direct tracks, wear on occlusal interferences and the preparation of slopes in inclined planes using composite resin, in order to promote the occlusal balance, performed with 21 children from 3 to 6 years of age studing in the Municipal Schools of Basic Education of a Brazilian municipality. Using a graphite tip, the reference points were marked on each gypsum model of both arcs, the intercanine and intermolar distance s to measure with a digital caliper. Panoramic radiographs were marked cephalometric points of the mandibular branch performed with ImageJ software. In the data analysis the software Bioestat 5.0 and Graphpad prism 7.0 were used. In the analysis of the models, we evaluated the intercanine distances that the statistical significance of the measurements before and after the treatment in the superior models, with value of p <0.0001. In the lower models for the same measure with p value <0.0044. In the intermolar evaluation, here was statistical significance only for the upper measurements p <0.0027. In the radiographic analysis, the cephalometric measures of condyle height at the base of the mandible and width were evaluated, being the right width before and a fter with p value <0.0918 and left with a p <0.0149. At the end of the treatment the difference between the right and left widths was p <0.0001 and the difference of the heights of p <0.0002. The difference between the height and the width of the right and left sides at the beginning was greater than the end of the treatment, which shows the previous growth was asymmetric and after the uncrossing, a symmetrical growth. It was concluded that the functional cross - bite was corrected by the treatment of the planas direct tracks, favorable clinical result was achieved, which demonstrated the effectiveness of the technique, and because of easy execution and use of daily dental materials, should be applied in public service and in private.